The Role of Guidance and Counseling Teachers in the Implementation of Independent Curriculum in Indonesia - Offando, Ocen; Firman, Firman; Sidik, Mohd Suhadi Bin Mohammad (Widyagogik, 2023)
This article explores the key role played by guidance and counseling teachers in the implementation of Merdeka Curriculum in Indonesia. Merdeka Curriculum is a recent educational innovation that emphasizes the development of life skills, creativity and independent thinking. This research outlines the role of guidance and counseling teachers in providing psychosocial support to students, helping them identify interests and talents, and providing career guidance in accordance with the demands of the Merdeka Curriculum. The method of writing the article refers to literature reviews such as books and the results of relevant articles. The findings in this study reveal that the implementation of the independent learning curriculum serves as a relevant and appropriate guide, requiring counseling teachers as the main implementers to ensure its efficiency.